Information technology and its’ modernization, the Internet, and sport psychology - Mishal Sohail; Muhammad Talha; Munib Ali, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
This research aims to describe information technology and its' modernization, the Internet, and sports psychology. A research study based on primary data collected used open-ended and closed-ended questions related to the variable and defined Internet modernization and sports psychology. This research study determines by smart PLS software. It generates a different result, including indicator correlations, discriminant validity, model fitness analysis, composite reliability, and an intelligent PLS Algorithm model related to the variables. Information technology is the leading independent variable. The Internet and sports psychology are both dependent variables. The result found that information technology presents significant and positive relation to the modernization of the Internet. Information technology also shows the direct impact and significance of sport psychology It plays a vital role in the modernization internet also sports psychology performance.